Pengembangan Sistem Informasi Rental Mobil dengan Metode Waterfall - Achmad Fauzi; Dedy Priyatna; Muhammad Rizky Julianto; Syahvira Kusumawati; Aries Saifudin; Teti Desyani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
In the current era of development of various technologies, related to the passage of the era of globalization which can greatly help and facilitate work and perform various activities, for example to check car rental prices. So it can be seen that with the technology and design that we have made, it will make it easier to do work and help market the available cars. As one of the businesses engaged in Car Rental Sembodo Rent Car is here to meet these needs by designing the latest system, which uses the waterfall method in making its website. The use of a system like this can make Sembodo Rent Car easier for workers and customers and make Sembodo Rent Car's turnover much bigger than before.